hNET as a target for neuroblastoma nanomedicine - Charousová, Markéta; Dostálová, Simona; Haddad, Yazan Abdulmajeed Eyadh; Strmiska, Vladislav; Křížková, Soňa; Hynek, David; Milosavljević, Vedran; Adam, Vojtěch; Heger, Zbyněk (Mendel University in Brno, 2017)
Chemotherapy often results in various side effects, which can negatively affect health. Neuroblastoma, one of the most common types of childhood cancer, is but one of the examples, where side effects of chemotherapeutic treatment lower the quality of patient's life. Modern way how to fight that is to enclose cytotoxic drug into some nanocarrier and its targeting to receptors overexpressed in membranes of cancer cells. Apoferritin (Apo), a natural protein cage, is very suitable as a nanocarrier, as it has no toxicity, immune system does not react to it, and drug can easily be loaded into its cavity. We enclosed ellipticine, clinical tested anti-cancer drug, into Apo cavity (creating ApoElli). The percentage of encapsulation was 61 % and size and transmission electron microscopy analysis showed the preserved Apo ~12 nm icosahedral structure after this encapsulation. Then we modified Apo outer surface with in silico-modelled peptides with hNET affinity and tested its toxicity and hemolytic activity. ApoElli modified with anti-hNET peptides was able to internalize into neuroblastoma cells and to deliver the drug. However, it proved to be safe for human RBC, unlike pure ellipticine, which caused observable hemolysis at the same concentration.

Chemotherapy often results in various side effects, which can negatively affect health. Neuroblastoma, one of the most common types of childhood cancer, is but one of the examples, where side effects of chemotherapeutic treatment lower the quality of patient's life. Modern way how to fight that is to enclose cytotoxic drug into some nanocarrier and its targeting to receptors overexpressed in membranes of cancer cells. Apoferritin (Apo), a natural protein cage, is very suitable as a nanocarrier, as it has no toxicity, immune system does not react to it, and drug can easily be loaded into its cavity. We enclosed ellipticine, clinical tested anti-cancer drug, into Apo cavity (creating ApoElli). The percentage of encapsulation was 61 % and size and transmission electron microscopy analysis showed the preserved Apo ~12 nm icosahedral structure after this encapsulation. Then we modified Apo outer surface with in silico-modelled peptides with hNET affinity and tested its toxicity and hemolytic activity. ApoElli modified with anti-hNET peptides was able to internalize into neuroblastoma cells and to deliver the drug. However, it proved to be safe for human RBC, unlike pure ellipticine, which caused observable hemolysis at the same concentration.
hNET as a target for neuroblastoma nanomedicine
Keywords: Ellipticine; hemolysis; nanoconstruct; neuroblastoma; toxicity; Ellipticine; hemolysis; nanoconstruct; neuroblastoma; toxicity